ANALISIS PENGINTEGRASIAN PENDIDIKAN BUDAYA DAN KARAKTER BANGSA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 PALEMBANG - Wina Fretty S; Ikbal Barlian; Siti Fatimah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The problems formulated are the values of culture and what characters are integrated and how the integration of cultural education and character of the nation on economic subjects in SMA Negeri 1 Palembang viewed from the aspects of teacher activity and the characters that appear in the learners in the process of learning in the classroom. The objective of the research is to know the cultural values and character of any nation that is integrated in economic subjects and to know the integration of cultural education and the character of the nation on economic subjects viewed from the aspect of teacher activity and the characters that appear in the learners in the learning process in the classroom. The population in the research is all the economic teachers who teach in the class X. Data collection techniques used observation to find out how the integration of cultural education and the character of the nation on economic subjects that viewed from the aspects of teacher activity and the characters that appear in learners in the learning process. From the observation result can be seen teacher activity in learning process including good category with percentage of average 65.24%. While the characters that appear in the learners in the process of learning in the class on economic subjects is the average percentage of 78.46% and categorized well. Thus, the integration of cultural education and the character of the nation on economicsubjects in SMA Negeri 1 Palembang has beendone well. Researchers suggest for teachers to further emphasize the cultural values and character of the nation to learners into any material that is learned so that it can be applied at the learning process as well as in everyday life and form a good personal character on the learners.